Pattern of Injuries in Motorbike Accidents (Journal of Pakistan Orthopaedic Association, 2018)
Objective: To determine the different pattern of injuries and their frequency in motor bike accidentsMethods: This Case series study was conducted at Department of Orthopedics, Jinnah Post Graduate Medical Centre(JPMC), Karachi, from January 2017 to December 2017. Patients aged 5-65 years, any gender and every kind of injury were included in the study.  Pathological fractures and concealed injuries were excluded. Patients were admitted through Accident & Emergency Department of JPMC and informed consent was taken. Injuries were divided in different regions. Examination and required investigations were done. Injuries were recorded in proforma. Statistical analysis was done using SPSS version 18.Results: Two thousand  patients were included. Mean age was 29.6 years. 1588 (79.4%) were males and 412 (20.6%) females. Male to female ratio was 3.85:1.A total of 684 (34.2%) patients were between age 16-30 years and 512 (25.6%) between 31-40. Lower limb injuries were 1136 (56.8%) while upper limb injuries were 544 (27.2%). Abrasions were 1874 (93.7%), lacerations 1362 (68.1%) and bruises 1040 (52%). Fractures in lower limb were 450 (22.5%) and upper limb 272 (13.6%)Conclusion: Younger males were more prone to motorbike injuries. Lower limb abrasions and fractures were the most common injuries.